The Relationship of Antenatal Care Frequency and Incidents of Stunting in Toddlers in Indonesia (Advanced Analysis of Riskesdas 2018) - Frisca Ronauli Batubara; Indah Paskahila Rindawa Mus; Ida Bagus Eka Utama Wija (Indonesian Journal of Global Health Research, 2025)
Stunting is a growth disorder in children which is measured by the child's height which is indicated by a z-score below -2 SD of the growth standard according to WHO. One of the risk factors that can cause stunting is the frequency of antenatal check-ups. Antenatal examination (ANC) is a health service provided to pregnant women, by the provisions of Minister of Health Regulation Number 97 of 2014. The 2018 Riskesdas data obtained from 34 provinces, 416 regencies, and 98 cities in Indonesia was used in this study. It was then further processed by the authors at the Faculty of Medicine, Christian University of Indonesia, in July 2024. This study further analyzes the 2018 Basic Health Research (Riskesdas) data. A cross-sectional method was used in this study, considering the data collection of research variables obtained at a specific point in time, by Riskesdas. Diagnostic testing was then used to determine whether there is a relationship between the frequency of antenatal care visits and the incidence of stunting in toddlers in Indonesia. Based on this study, 49,283 pregnant women underwent antenatal check-ups according to the criteria, while 6,206 did not meet the criteria. Among toddlers, 15,192 children experienced stunting, while 40,297 did not. The chi-square test results showed a p-value of <0.001, which is less than 0.05, indicating that, statistically, there is a significant relationship between the frequency of antenatal check-ups during pregnancy and the occurrence of stunting in toddlers. Based on data processing and discussion, this study concludes that there is a relationship between the frequency of antenatal care (ANC) visits by pregnant women and the occurrence of stunting in toddlers, with a p-value of <0.001 and an odds ratio of 0.826. This p-value indicates a strong relationship between the frequency or number of antenatal visits and the occurrence of stunting. This means that the likelihood of stunting occurring is 0.826 times higher compared to those who undergo antenatal check-ups according to the standard.